Children of Shadows - Kramer, Karen (United States, 2001)
Soros Documentary Fund In Haiti, due to poverty many parents are forced to give away their children who, sometimes as young as four, go to live and work for other families as live-in, full-time, unpaid domestic servants, virtually slaves. This documentary portrays the “restavek” children of Haiti and follows them as they go through their daily chores – the endless cycle of cooking, washing, sweeping, mopping, marketing, fetching water, and running errands. The children speak about the lives they are forced to lead while their “aunts” (adoptive caretakers) speak proudly of the vast mountain of work that “their” restavek do for them. The filmmaker goes to the countryside to interview the families of the children and to find out what kind of situation would force them to give away one or more of their children. She also interviews several Haitian social workers and economists on the causes favoring such a situation. A film about the economic despair and its effects on children in Haitian society.